2018
DOI: 10.3906/sag-1710-93
|View full text |Cite
|
Sign up to set email alerts
|

Detection of CCND1 , C-MYC , and FGFR1 amplification using modified SYBR Green qPCR and FISH in breast cancer

Abstract: Our findings revealed that the applied qPCR approach could precisely quantify the relative gene copy number. More studies with a larger sample size are suggested to confirm the clinicopathological value of CCND1 , C-MYC , and FGFR1 amplification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This meta-analysis included 18 studies comprising 6400 patients. Of these, 1136 (18%) had CCND1 amplified tumours, which is within the 10-35% range generally reported (2)(3)(4). Previous evidence suggested an association between CCND1 amplification and ER positive status (4,13,15,51).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…This meta-analysis included 18 studies comprising 6400 patients. Of these, 1136 (18%) had CCND1 amplified tumours, which is within the 10-35% range generally reported (2)(3)(4). Previous evidence suggested an association between CCND1 amplification and ER positive status (4,13,15,51).…”
Section: Discussionmentioning
confidence: 53%
“…Interestingly, one study showed that cyclin D1 immunostaining with an Allred score of >6.5 (57) was predictive of CCND1 amplification in ER positive BCa patients, with high sensitivity (94.2%) and specificity (87.8%) (13). This is somewhat surprising, given that CCND1 amplification occurs in 10-35% of BCa tumours (Table 1), and cyclin D1 overexpression occurs in 50-70% of BCa tumours (2)(3)(4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation